2023
DOI: 10.3390/jpm14010049
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of Therapy in High-Grade Serous Tubo-Ovarian Cancer—The Possibility or the Necessity?

Jacek Wilczyński,
Edyta Paradowska,
Miłosz Wilczyński

Abstract: High-grade serous tubo-ovarian cancer (HGSTOC) is the most lethal tumor of the female genital tract. The foregoing therapy consists of cytoreduction followed by standard platinum/taxane chemotherapy; alternatively, for primary unresectable tumors, neo-adjuvant platinum/taxane chemotherapy followed by delayed interval cytoreduction. In patients with suboptimal surgery or advanced disease, different forms of targeted therapy have been accepted or tested in clinical trials. Studies on HGSTOC discovered its geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 102 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…For instance, those with early disease stages, type I tumours and lower baseline CA-125 levels usually have higher survival [12,[83][84][85][86][87][88]. However, ongoing research has recently identified several molecular biomarkers associated with OC treatment response and prognosis, including mutations, gene expression patterns, and/or epigenetic changes [89][90][91]. This is particularly relevant given the high heterogeneity that characterises HGSC, with the predominant and most lethal OC subtype accounting for 70% of OC-related deaths [92].…”
Section: Disease Diagnosis and Prognosis Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, those with early disease stages, type I tumours and lower baseline CA-125 levels usually have higher survival [12,[83][84][85][86][87][88]. However, ongoing research has recently identified several molecular biomarkers associated with OC treatment response and prognosis, including mutations, gene expression patterns, and/or epigenetic changes [89][90][91]. This is particularly relevant given the high heterogeneity that characterises HGSC, with the predominant and most lethal OC subtype accounting for 70% of OC-related deaths [92].…”
Section: Disease Diagnosis and Prognosis Assessmentmentioning
confidence: 99%
“…Since the proposal of these models, the integrative analysis of tumour (epi)genetic and molecular signatures has more or less confirmed the existence of these four HGSC subtypes with an impact on prognosis and/or treatment response (Table 1). This is anticipated to change OC management by facilitating personalised treatment [91]. Abbreviations: HRR, homologous recombination repair; NGS, next-generation sequencing; PFS, progression-free survival; TCGA, The Cancer Genome Atlas.…”
Section: Disease Diagnosis and Prognosis Assessmentmentioning
confidence: 99%
See 1 more Smart Citation